Modeling of Temperature Mode of the Soil - Oralkhan, Sultashova (International Journal of Psychosocial Rehabilitation, 2020)
The article shows the prospects of applying the methods of mathematical physics to the study of the features of the temperature regime of soil. On the basis of a homogeneous heat equation with in homogeneous boundary conditions, the possibility of mathematical modeling of the propagation of a thermal wave deep into the soil with the aim of studying its thermal regime depending on external factors is considered.